1997
DOI: 10.1038/sj.onc.1201327
|View full text |Cite
|
Sign up to set email alerts
|

Induction of telomerase activity by UV-irradiation in Chinese hamster cells

Abstract: Telomerase is a ribonucleoprotein whose activity has been detected in germline cells and in neoplastic and immortal cells. Telomerase compensates the telomere loss arising by the end replication problem by synthesizing telomeric repeats at the 3' end of the eukaryotic chromosomes. Telomerase is reactivated during cancer progression in human and mice. In order to determine whether the telomerase activity can be upregulated in vitro in response to DNA damaging agents, we examined the telomerase activity in ®ve C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
16
1

Year Published

2001
2001
2007
2007

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 23 publications
4
16
1
Order By: Relevance
“…Early upregulation has previously been reported in irradiated mouse and human hematopoietic cell lines. 26,31 In agreement with our results, several radiation studies also noted large increases in telomerase activity 24 h after treatment, as well as dose-dependent hyperactivation [26][27][28]31,32 that plateaus at higher doses. 26,28 The magnitude of telomerase upregulation observed in our study is similar to the increases in activity reported for X-irradiated human colorectal carcinoma cell lines.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Early upregulation has previously been reported in irradiated mouse and human hematopoietic cell lines. 26,31 In agreement with our results, several radiation studies also noted large increases in telomerase activity 24 h after treatment, as well as dose-dependent hyperactivation [26][27][28]31,32 that plateaus at higher doses. 26,28 The magnitude of telomerase upregulation observed in our study is similar to the increases in activity reported for X-irradiated human colorectal carcinoma cell lines.…”
Section: Discussionsupporting
confidence: 81%
“…One hypothesis is that telomerase upregulation may constitute part of the cellular response to DNA damage, as telomerase upregulation has been reported only in cells exposed to DNA-damaging treatments such as radiation. [26][27][28][31][32][33] This hypothesis is supported by our data, which showed that telomerase upregulation occurred only in cells that undergo an extensive period of cell cycle arrest prior to cell death, a type of response that is characteristic of the DNA damage repair process. 42 Double-stranded DNA breakinducing treatments result in broken chromosomes that may mimic exposed or dysfunctional telomeres.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Induced telomerase activity progressively decreased in FHIOSE cells by 48 h after UV or DMSO treatment, while induced telomerase activity in SW626 cells returned to controls levels by 24 h after treatment. These results are in agreement with previous observations reporting a strong association between telomerase activity with sun exposure [53], a UV dose-dependent induction of telomerase activity in CHO cells [54], and restoration of basal telomerase levels within 24 h following withdrawal of DMSO [61]. We used our model system to identify some of the components that may regulate telomerase activity.…”
Section: A Htrt Iihtrsupporting
confidence: 81%
“…UV and DMSO were deemed to be potential modulators of telomerase activity in ovarian epithelial cell lines based upon our current understanding of telomerase regulation and ovarian neoplastic progression. Specifically, since Ueda et al reported increased telomerase activity following UV exposure of normal skin [53] and Hände et al reported a dose-dependent increase in telomerase activity following UV treatment in CHO cells [54], we sought to determine whether UV could induce telomerase activity in ovarian epithelial cell lines. Further, in contrast to carcinomas of most other tissues that de-differentiate with neoplastic progression, ovarian cancer progression is associated with the acquisition of morphological features characteristic of the endocervix, endometrium, and oviduct owing to their common embryonic origin [55][56][57].…”
Section: Discussionmentioning
confidence: 99%